TRAINER KIT MOTOR BLDC SEBAGAI MEDIA PEMBELAJARAN - Dwi Meilani; Sukir Alida Saputra; Andik Setiawan, I Made; Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Technological advancements in the industry and electrical fields have led to almost all equipment requiring electricity. Electric motors,which convert electrical energy into mechanical energy,are continuously evolving to enhance efficiency and performance. BrushlessDC (BLDC) motors are one type of motor used in various industries due to their high efficiency, high torque, and low noise. Unlike conventional DC motors, BLDC motors use electronic commutation, resulting in smoother rotation and lower noise. The purpose of this research is to design and develop a BLCD Motor Trainer Kit that includes key components such as the BLCD motor, microcontroller control (Arduino Uno), Programming, interfacing. This model allows students to understand the basic concepts, working principles, and applications of BLCD motors in real-time, as well as develop practical skills. The integration of this Trainer Kit into the curriculum is expected to enhance students’ understanding of Brushless DC motors.